Susceptibility of Beans and Maize Grains to Insect Infestation among Vendors in Boluwaduro Local Government, Osun State, Nigeria - Abdulbaki, Mudashir Kijan; Lateef, Saheed Adekola; Fadairo, Oyindamola Elizabeth; Olaiya, Joy Olamide (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
Grain infestation by insects is a widespread issue globally and traditional methods of storage usually enhance this challenge among local vendors. This study aimed to determine the susceptibility of beans grain to insect infestation among vendors in Boluwaduro Local Government, Osun State, Nigeria. A multi-stage sampling procedure was used to select three beans and maize grains vendors in the three different markets; Igbajo, Otan Ayegbaju and Iresi (one in each district) in the study area. An interview approach was used to obtain the beans and maize grains history from the three randomly selected vendors in the selected and a measure of each of grains were purchased separately and transported to Science Laboratory Technology (SLT), Igbajo Polytechnic, Igbajo, Osun State for entomological analysis (insect infestation, insect emergence, percentage weight loss and percentage economic loss) were determined. Sack and chemicals are used by majority of the vendors for storage and preservation respectively. The result showed that only Callosobruchus maculatus affected the beans in the study and Iresi has the lowest insect infestation (a total of 3 insects) while 3 species (Sitophilus zeamais, Prostephanus truncatus, and Tribolium castaneum) were found in the maize, with Iresi also the location with lowest infestation (only 1 insect). Two vendors from Iresi have the lowest emergence (<3 insects emerged) and percentage seed damage (<25% grains damaged) for beans while Igbajo and Iresi have lowest emergence (<7 insects emerged) and percentage seed damage (<18% grains damaged). A vendor in Iresi has the lowest percentage weight loss (<10%) for both beans and maize grains, and the economic losses recorded for beans (>60%) are greatly higher when compared to maize (<50%). To address these challenges, it is crucial for vendors to adopt Integrated Pest Management (IPM) during the storage.